Does integral affect influence intentions to use artificial intelligence for skin cancer screening? A test of the affect heuristic. - Tong, Stephanie Tom; Sopory, Pradeep (Psychology & Health, 2019)
Objective: This study investigated how affect influences people's processing of messages about risks and benefits of using autonomous artificial intelligence (AI) technology to screen for skin cancer. We examined integral affect (emotion derived during decision making) separately from incidental affect (extraneous mood states). Design: Using the affect heuristic framework, we randomly assigned 273 participants to conditions featuring risk (high, low, uncertain) or benefit (high, low, uncertain) messages about AI. Following 'affect-as-spotlight', we also explored whether people's integral affect towards skin cancer moderated the relationship between risk/benefit messages and AI screening intentions. Outcomes: Perceived risk, perceived benefit, positive and negative affect toward AI, intention to use AI screening. Results: After controlling for incidental affect and risk perceptions, we found that compared to low risk messages, uncertain risk messages increased participants' negative affect toward AI, decreased positive affect toward AI, increased AI risk evaluations and reduced AI benefit evaluations. Perceptual variables significantly mediated participants' intentions to use AI for risk messages but not benefit messages. No moderation effects were found. Conclusions: Results suggest extending the affect heuristic framework to include uncertain risk conditions. Integral AI affect influenced people's interpretation of messages, which then impacted likelihood to use AI technology for health.